Super-high-resolution aerial imagery, digital surface model and 3D point cloud of Selawik Village, Alaska - Tabea Rettelbach; Ingmar Nitze; Inge Grünberg; Jennika Hammar; Simon Schäffler; Daniel Hein; Matthias Gessner; Tilman Bucher; Jörg Brauchle; Jörg Hartmann; Torsten Sachs; Julia Boike; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at a spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR at 5.81 pts/m^2 and 2.35 pts/m^2, respectively. This dataset covers approximately 5.74 km^2 of Selawik Village in Alaska, with all images collected on 1 July 2021. This super-high-resolution dataset provides opportunities for generating detailed training datasets of permafrost landform inventories, a baseline for change detection for thermokarst and thermo-erosion processes, and upscaling of field measurements to lower-resolution satellite observations.